Ratio of CO2 and O-2 as index for categorising soil biological activity in sugarcane areas under contrasting straw management regimes - Almeida, Risely Ferraz de [UNESP]; Teixeira, Daniel de Bortoli; Montanari, Rafael [UNESP]; Bolonhezi, Antonio Cesar [UNESP]; Teixeira, Edson Belisario [UNESP]; Moitinho, Mara Regina [UNESP]; Panosso, Alan Rodrigo [UNESP]; Spokas, Kurt A.; La Scala Junior, Newton [UNESP] (Csiro Publishing, 2018)
This study was developed in a sugarcane area under contrasting management regimes defined by mechanical green harvesting (GH) and burning harvesting (BH) to test the hypotheses that the ratio of carbon dioxide (CO2) and oxygen (O-2), known as the apparent respiratory quotient (ARQ), can be used to categorise soil biological activity. The study aimed to (i) examine the profile and relationship between the CO2 flux (FCO2) and the O-2 flux (FO2) in a sugarcane area under mechanical harvesting with straw burning (BH) and mechanical harvesting with maintenance of straw (GH), considering soil moisture; (ii) and suggest the use of ARQ as an index for categorising the biological activity of soils. Our results showed consistently lower FCO2 for soil moisture in the range of 6.0-8.6% for both management regimes. The soil moisture increments triggered a decrease in FO2 and an increase in FCO2 and ARQ. The FCO2 and FO2 were positively correlated under BH. The BH yielded a cumulative CO2 emission of 53.68% higher than for GH. Overall, our findings revealed that soil moisture affected the O-2 uptake and CO2 emission profile of soil, limiting O-2 uptake and increasing CO2 releases for water-filled porosity below 70%. The GH management system, which incorporates sugarcane residues into the superficial layer of the soil, can help protect against soil erosion. The ARQ can be used as an index to categorise biological activity in soil, where ARQ values close to 1 can be considered a reflection of aerobic activity with balance between CO2 production and O-2 consumption.
Keywords: CO2 emission; sugarcane straw management; O-2 uptake; respiratory quotient; soil biological activity